Balloon atrioseptostomy under echocardiographic and fluoroscopic guide in patients with congenital heart diseases under 3 months in a national reference pediatric cente - Catalán Cabrera, Alex (2024)
Objective. Balloon atrioseptostomy is an emergency procedure in congenital heart diseases requiring an atrial septal defect to increase cardiac output in right-sided obstructive lesions or to improve mixing in patients with transposition of the great arteries. This procedure is currently performed with both fluoroscopy and echocardiography. The main objective is to describe our experience with the use of balloon atrioseptostomy under echocardiographic and fluoroscopic guidance in patients under 3 months. Materials and methods. A descriptive, comparative and retrospective study in patients in whom balloon atrioseptostomy was performed under echocardiographic and fluoroscopic guidance between 2018 and 2023 in a referral hospital in Peru. Results. 36 patients were analyzed, of which 21 were from the fluoroscopy group. and 15 patients from the echocardiography group. More than 2/3 of the cases were males, and more than 60% of patients in both groups had transposition of the great vessels. No significant differences were found in terms of ventilatory support and inotropic support. The success of the procedure was 100% in both groups, without complications. Conclusion. Both balloon atrioseptostomy performed by fluoroscopy and those performed by echocardiography were successful and without complications, emphasizing that the one performed by echocardiography is performed in the patient’s crib, avoiding the transfer of the critical unit to the angiography room and without the use of radiation.